Didactical Suggestions to Implement a Leveling Course in Mathematics: Systematization of an Experience at the National University of Costa Rica - Picado-Alfaro, Miguel (2018)
This paper presents the results of a study on the systematization of an experience based on the implementation of a leveling course in mathematics at the School of Mathematics of the National University of Costa Rica. This course is addressed to high school students, college students, and the general public; it approaches certain topics on real numbers and the fundamentals of algebra, which constitute the base of the mathematical formation in college education and whose understanding stands out as a cognitive limitation of college students. The objective of the study was to evaluate the design and development processes of the course and assessed its achievements in the participating population in order to obtain inputs for curricular noticing and decision making on its design and implementation in later years. Regarding the methodology, the study was framed in qualitative-descriptive research; the anecdotal records of the tutor-teacher were the instruments to collect information. Categories were defined in a process of systematization of experiences, and the units of analysis were defined from relevant aspects of the course to analyze the information. The systematization of this experience and its analysis have allowed the identification of cognitive and motivational specificities in the students, as well as methodological and evaluative particularities in the teachers. Also, from the results based on critical interpretation, some suggestions were proposed; these suggestions are addressed to the offer of the course and the curricular changes that can be made to improve its design and the student’s learning during the sessions.